Perceptions of who is in the healthcare team? A content analysis of social media posts during COVID-19 pandemic. Issue 5 (2nd September 2020) - El-Awaisi, Alla; O'Carroll, Veronica; Koraysh, Somaya; Koummich, Sarra; Huber, Marion
ABSTRACT: Social media posts can be used to explore public perceptions of interprofessional teams and healthcare professionals. The aim of this study was to use social listening technique to explore unfiltered public perceptions of the professionals involved in healthcare teams during the COVID-19 pandemic, in a naturalistic online setting, and to elaborate on the emotional reactions in response to an online social media post. A cross-sectional retrospective review of comments on a specific social media post was conducted between 15 March and 28 April 2020 using summative content analysis. One image that was widely circulated on social media platforms with two questions: 'Who society thinks works at hospital? versus who really works at hospitals?' was selected. Three platforms were searched, Facebook®, Twitter®, and LinkedIn®. Only publicly available posts were included. Out of the initial 40 posts identified, 21 posts which had 1759 comments were analysed and 1576 were included for coding. Of the emerging nine themes, perceptions of who is in the team was the largest (40.5%, n = 639), followed by agreement (23.1%, n = 364) and feeling excluded (16.2%, n = 255). Of emotional expressions, 42.1% were positive and 57.9% negative. The most frequent emotions were frustration (54.4%, n = 857) followed by gratitude (16.3%, n = 257) and relief (15.9%, n = 250). The post brought considerable attention to the role of the interprofessional team and generated many feelings of frustration and exclusion. For this reason, the response to this social media post is very important and not to be overlooked. Healthcare professionals need to work together to strengthen their presence as an interprofessional team, united to deliver safe effective quality care for patients. The current COVID-19 pandemic and the media attention should be taken as an opportunity by the interprofessional community to work together to combat negative media stereotypes. Further research is warranted on public perceptions of the healthcare team.